2013
DOI: 10.1177/1363461513501712
|View full text |Cite
|
Sign up to set email alerts
|

Mood and anxiety problems in perinatal Indigenous women in Australia, New Zealand, Canada, and the United States: A critical review of the literature

Abstract: We conducted a review of research literature related to anxiety, depression, and mood problems in Indigenous women in Canada, the United States (including Hawaii), Australia, and New Zealand. Quantitative and qualitative research studies published between 1980 and March 2010 were reviewed. The initial search revealed 396 potential documents, and after being checked for relevance by two researchers, data were extracted from 16 quantitative studies, one qualitative research article, and one dissertation. Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
(62 reference statements)
5
27
0
Order By: Relevance
“…The first is similar to rates reported in a review study of 6.5% for major depression and 14.5% for major and minor depression combined (Gavin et al, 2005), as well as rates reported in other Australian research studies (Bowen et al, 2014). When a composite variable was created (major depression present and/or in receipt of an antidepressant medication and therefore capturing women who had been depressed/distressed but presumably responded to medication) the prevalence rate of 10.6% was in the PND range noted in the Section 1 of 10-15%.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The first is similar to rates reported in a review study of 6.5% for major depression and 14.5% for major and minor depression combined (Gavin et al, 2005), as well as rates reported in other Australian research studies (Bowen et al, 2014). When a composite variable was created (major depression present and/or in receipt of an antidepressant medication and therefore capturing women who had been depressed/distressed but presumably responded to medication) the prevalence rate of 10.6% was in the PND range noted in the Section 1 of 10-15%.…”
Section: Discussionsupporting
confidence: 83%
“…Predicting those likely to develop post-natal depression (PND) is an important public health and clinical priority, with the condition quantified as affecting 10-15% of mothers in international reviews (Markhus et al, 2013) and 8-12% in Australian studies of respective non-indigenous and indigenous women (Bowen et al, 2014). Post-natal depression is commonly diagnosed using DSM criteria with the specifier "with peripartum onset," or by use of specifically designed dimensional measures.…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico exist different organizations focused to vigilance the violence of pregnant women, specifically in rural and indigenous zones, because the prenatal period supposes a vulnerable time lapse characterized by major susceptibility to depress, which is a pathology more disabling in a critical period of all women the witch needed self-care and care for her baby. The prevalence of depression in pregnancy and puerperal period is around 10-20%, in agree to various authors [8][9][10], however, little studies have been published related with indigenous women [11] and, few studies or none has been published for pregnant indigenous Mexican women. In regard to satisfaction surveys about life quality, although appear to be subjective methods, these can offer wellness, self-perception data and suggest a comparison point with other populations [12].…”
Section: Introductionsupporting
confidence: 59%
“…are resilient and report excellent or very good health [17][18][19][20]. Some evidence suggests that social support might play a role in the resilience of Indigenous people.…”
Section: Introductionmentioning
confidence: 99%